2010
DOI: 10.1017/s0024282910000563
|View full text |Cite
|
Sign up to set email alerts
|

Optimal sample sizes and allelic diversity in studies of the genetic variability of mycobiont and photobiont populations

Abstract: Population genetic studies of lichen-forming fungi and their algae require appropriate sampling schemes that ensure representative sampling of the genetic variability. One question is whether mycobiont and photobiont populations require different sampling strategies. Here, I applied rarefaction methods to a dataset containing three microsatellite loci of Lobaria pulmonaria and three microsatellite loci of its green-algal photobiont, Dictyochloropsis reticulata. I analysed the sample sizes required for 1) the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Although the pattern of spatial autocorrelation in genotype diversity was similar in the symbionts, one emerging difference was that gene diversity was slightly higher in the algal than in the fungal data, consistent with the results of rarefaction analyses of a subset of fungal and algal microsatellite markers (Werth 2010a). Moreover, our result of higher diversity in the photobiont is in agreement with the pattern found in other lichen symbioses (Blaha et al 2006;Muggia et al 2008;Ohmura et al 2006;Opanowicz and Grube 2004;Werth and Sork 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Although the pattern of spatial autocorrelation in genotype diversity was similar in the symbionts, one emerging difference was that gene diversity was slightly higher in the algal than in the fungal data, consistent with the results of rarefaction analyses of a subset of fungal and algal microsatellite markers (Werth 2010a). Moreover, our result of higher diversity in the photobiont is in agreement with the pattern found in other lichen symbioses (Blaha et al 2006;Muggia et al 2008;Ohmura et al 2006;Opanowicz and Grube 2004;Werth and Sork 2010).…”
Section: Discussionsupporting
confidence: 89%
“…For both symbionts of L. pulmonaria , it has been shown that sample sizes of 20 individuals allows one to describe most of the allelic diversity at the population level, while within landscapes 300–400 samples and about 25–30 populations are sufficient (Werth ). The main goal of this study was to reconstruct the common phylogeographic patterns shared between the symbionts of L. pulmonaria and to localize centres of genetic differentiation on large spatial (and temporal) scales.…”
Section: Discussionmentioning
confidence: 99%
“…2005). On average, 31 thalli were collected per population, which has been found to be an appropriate number to resolve within‐population mycobiont and photobiont genetic structure (Werth 2010).…”
Section: Methodsmentioning
confidence: 99%